Women in leadership- Experiences of advancements, stereotypes and discrimination in a corporate environment - Baxter, Kayleigh (The IIE, 2017)
The purpose of this research is to explore the experiences of women in relation to advancement, stereotypes, and discrimination in a corporate environment. Women in the workplace are not equally represented when compared to men and women are still underrepresented as leaders in the 21st century. An interpretivist, qualitative approach was used in this study. This study aimed to answer these research questions. Firstly, how females in corporate environments feel about the nature of the corporate environment. Secondly, to what extent are females in the corporate environment supported in order to advance their careers. Lastly, do women working in the corporate environment feel that they are treated equally and equally compensated when compared to male employees. Through a focus group the following theme were identified: The ‘Harsh’ Corporate Environment, Family Responsibility, Limitations to Career Advancement, Salary Discrimination and Male versus Female Support. Overall in the 21st century women in a corporate environment find the nature of the corporate environment harsh and these women were still subject to indirect discrimination. Women are still held back by stereotypes and because of this they battle to advance in their careers.
Keywords: Gender equality; Discrimination; Corporate environment